La difícil tolerancia - D'agostino, Francesco (Revista Española de Pedagogía, 2018)
Nowadays toleration is often understood as a pragmatic principle leading social coexistence. In this way, it becomes something extremely fragile. Instead, the authentic toleration has a strong hermeneutical justification: truth doesn't appear but in the many and irreducible historical, psychological and cultural diversity of human experiences. Tolerating diversity means respecting the hermeneutical property of truth. Toleration has its limits. An empiric criterion to individualize the tolerable diversity is the claim to rights, because that who claims a right pretends this claim to be, if not universal, at least general.
Keywords: tolerancia; Revista Española de Pedagogía